Artificial Intelligence in Governance: Opportunities for Political Participation and Ethical Challenges - Mantiri, Jeane; Maria Siwi, Cynthia; Sani Putri, Intan; Hapsari, Nimas (Indonesian Association for Public Administration (IAPA), 2025)
The use of Artificial Intelligence (AI) in public administration presents both opportunities and challenges for governance. While AI can enhance political participation through data utilization, digital transparency, and public oversight, it also raises concerns over transparency, accountability, privacy, bias, and inequality. This study seeks to identify the dual role of AI in shaping political participation within governance. Using a descriptive literature review of studies and policy documents, the findings show that AI can expand citizen engagement beyond electoral processes but may also deepen participation gaps among social groups if ethical and inclusive governance frameworks are not ensured.